Characterization of Large Chromosome Segment Introgressions from Triticum turgidum subsp. dicoccoides into Bread Wheat with Simple Sequence Repeat Markers. Issue 4 (1st July 2013) - Zhou, Wei; Jiang, Yurong; Zhang, Wei; Xu, Guifang; Rong, Junkang
ABSTRACT: Libraries of large chromosome segment introgressions from wild relatives to crop species are valuable for assigning genes to specific chromosome segments and for interspecific transfers of useful genes. Using chromosome engineering, two sets of introgression lines (ILs) were created from chromosome segments of wild emmer [ Triticum turgidum L. subsp. dicoccoides (Körn. ex Asch. & Graebn.) Thell. (TDIC)] in two cultivars of bread what ( Triticum aestivum L.) by backcrosses to ditelocentrics. Segment identities were confirmed, and genetic lengths of segments and map positions of the translocation breakpoints were determined using 277 simple sequence repeat markers polymorphic between the recipients (bread wheat) and the wild donor (TDIC). The identities of all targeted chromosome arms in individual introgressions were confirmed. In addition, most lines also carried introgressed segments on nontargeted arms, most often the proximal parts of arms opposite to the targeted ones, which is consistent with the distribution of crossing over in wheat and are unavoidable when alien chromatin is introgressed by backcrosses to telocentrics. Using these ILs, some loci controlling important quantitative traits were located on specific TDIC chromosomes, such as loci with positive effects on thousand kernel weight (TKW) on chromosome arms 6AS, 4BS, 1BS, and 7A. These results indicate that these ILs might be a useful germplasm in allocating genes to chromosome arms and in wheat breeding.